Strategi Pengembangan Obyek Wisata Air Terjun Lacolla Kabupaten Maros: Lokasi Studi Dusun Malaka, Desa Cenrana Baru, Kecamatan Cenrana - Rusneni Ruslan; Andi Ike Nurhikmah; Agus Salim (Fakultas Teknik Universitas Bosowa, 2021)
This study aimed to identify factors that affecting to development of tourism in Lacolla waterfall and identify a strategy to development tourism potential in Lacolla waterfall, Maros Regency. This study uses a qualitative approach. The data obtained were analyzed by multiple linear regression and SWOT analysis. Based on this research, it was found that the variables of attractiveness, facilities, promotion, and accessibility had a significant effect on the development of Lacolla Waterfall, while infrastructure did not provide a significant effect. The strategy for developing Lacolla waterfall is to increase accessibility to support the development of tourism in the Lacolla waterfall attraction area; development of tourism destinations in the context of developing tourist attractions, building infrastructure, providing public facilities, and developing tourism facilities in an integrated and sustainable manner; maximizing potential management and nature conversation as well as increasing promotional activities for Lacolla waterfall; and involve the community to maintain security in the tourist area.